2016
DOI: 10.1016/j.jpowsour.2016.10.075
|View full text |Cite
|
Sign up to set email alerts
|

LiMPO4 and derived NaMPO4 (M = Mn, Fe, Mg) with excellent electrochemical properties for lithium/sodium ion batteries

Abstract: A simple two-step solid-state-reaction process is adopted to synthesize carbon-coated Mg-doped Li(Mn,Fe)PO 4 (LMMFP) nano-particles. As positive electrode materials for lithium-ion batteries, the carbon-coated LMMFP samples show excellent electrochemical properties in a temperature range from-20 to 55°C. For example, LiMn 0.48 Fe 0.5 Mg 0.02 PO 4 can deliver a capacity of 146.2 mAh g-1 at 3C rate and retain 95.3% after 450 cycles at 25°C. It can also deliver 160.7 mAh g-1 at 1C and retain 97.7% after 100 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…There were also some other iron phosphate–carbon composite materials. For instance, Liu et al reported a FePO 4 /rGO nanosheet through a microemulsion technique . It owns outstanding electrochemical performance, different capacity, and rate ability.…”
Section: Lithium Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…There were also some other iron phosphate–carbon composite materials. For instance, Liu et al reported a FePO 4 /rGO nanosheet through a microemulsion technique . It owns outstanding electrochemical performance, different capacity, and rate ability.…”
Section: Lithium Batterymentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. c,d,g) Reproduced with permission . Copyright 2014, Elsevier.…”
Section: Lithium Batterymentioning
confidence: 99%
“…have observed that, under N 2 atmosphere, the chain‐stripping elimination of H 2 O is completed at 350°C while PVA is converted into an un‐saturated aliphatic polymer, which is further decomposed into a char at 700–800°C with about 4% carbon residue . Such a considerable carbon residual behavior have attracted much attention from various research fields, especially for some battery electrode materials with a low electronic conductivity, such as LiFePO 4 and Li 3 V 2 (PO 4 ) 3 because it can form a carbon coating on the particles of these phosphate materials and significantly improve their electrochemical performances. Besides, the formation of un‐saturated polymer intermediate product upon the elimination of H 2 O from PVA is favorable to produce more graphitic carbon due to the presence of conjugating ‐C=C‐C=C‐ carbon chains.…”
Section: Figurementioning
confidence: 99%
“…It is acknowledged that the cathode materials play a key role in high-performance SIBs. Hence, the reports on cathode materials, such as Na x MnO 2 [10], NaFeF 3 [11], NaCrO 2 [12], NaMPO 4 [13,14], Na 0.67 Mn 0.65 Fe 0.2 Ni 0.15 O 2 [15], V 2 O 5 [16], used for sodium ion batteries is continuously growing. Among these, Na 3 V 2 (PO 4 ) 3 (NVP), a NASICON-structure with open three dimensional framework, has an excellent ionic conductivity and good thermal stability, allowing it to be used as a suitable cathode material for sodium ion battery systems [17].…”
Section: Introductionmentioning
confidence: 99%